NUMERICAL ANALYSIS SEAKEEPING AND MOTION SICKNESS INCIDENCE (MSI) ON HOSPITAL SHIPS BY ADDING FINS STABILIZER - Yasin, M; Ariani, Betty; Chandra Ariesta, Riski (Journal of Marine-Earth Science and Technology, 2021)
The development in maritime technology to improve ship performance and operations are growing and diverse. One of the developments carried out is the addition of fin stabilizers to improve ship safety as support for comfort and ships. This research analyzes the effect of variations in the shape of the fin stabilizer on the seakeeping and Comfort Index for Hospital Ships using Maxsurf Modeler software. The parameters used in this research are fins stabilizer Gemini 30, Gemini 50, and modular NR 30. While the variation of ship speed 0, 14, and 18 knots. The direction of the arrival of waves 0, 45, 90, 135, and 180 degrees. Based on data analysis carried out on ship motion, the NR 30 type fin stabilizer is far superior to the others with a maximum value of 4.04- degree roll movement, 0.543- degree pitch movement, and 0.4116 heave acceleration movement. Type NR 30 also has the best comfort on the moderate Motion Sickness Incidence (MSI) Criteria.